Corticobasal manifestations of Creutzfeldt-Jakob disease with D178N-homozygous 129M genotype. Issue 1 (1st January 2020) - Huang, Yumeng; Jianfang, Ma; Morales, Rodrigo; Tang, Huidong
ABSTRACT: Creutzfeldt-Jakob disease (CJD) is a prion disease, usually presented with memory loss, ataxia, dementia, myoclonus, involuntary movements and psychiatric problems. D178N-homozygous 129M genotype has been recognized in the diagnosis of fatal familial insomnia (FFI) globally. Here we report a patient presented with progressive left upper limb stiffness, bradykinesia, hypomimia and weight loss (10 kg) initially. She progressed to dementia, dysphasia, dysphonia and be bedridden quickly but did not present insomnia. She was diagnosed with CJD corticobasal subtype carrying a classic D178N-129M mutation of PRNP in FFI. Remarkably, she has a strong family history of neurological degeneration diseases but the other members of this pedigree who do not carry D178N-homozygous 129M mutation in PRNP do not present any CJD or FFI symptoms. We conclude that this patient carrying D178N-homozygous 129M mutation in PRNP should be diagnosed as CJD. Thus, the clinicopathology should be considered as a crucial evidence in diagnosing some cases, but FFI could be evaluated as a differential diagnosis with a unique clinical profile. List of abbreviations AD: Alzheimer disease; ADL: Activities of Daily Living; CBD Cortical basal degeneration; CBS: Corticobasal syndrome; CJD: Creutzfeldt-Jakob disease; DWI: Diffusion-weighted image; EEG: Electroencephalograph, fCJD: familial Creutzfeld-Jakob disease; FFI: Fatal familial insomnia; FLAIR: Fluid-attenuated inversion recovery; MMSE: Mini-mental state examination; MoCA: Montreal Cognitive Assessment; MRI: Magnetic resonance imaging; PD: Parkinson disease; PrP: Prion protein; PSWC: Periodic sharp wave complexes; SWI: Susceptibility-weighted imaging